Revision of the Venezuelan spider genus Stenosfemuraia González-Sponga, with new generic and specific synonymies (Araneae, Pholcidae) - Huber, Bernhard A.; Arias, Quintin C. (Zootaxa, 2017)
The Venezuelan genus Stenosfemuraia González-Sponga, 1998 is revised, with redescriptions of its three named species: S. parva González-Sponga, 1998 (type species); S. cuadrata González-Sponga, 2005; and S. pilosa (González-Sponga, 2005) n. comb. The latter species was originally described as Codazziella pilosa, and six years later again as Chichiriviche costanero González-Sponga, 2011 (n. syn.). The monotypic genera Codazziella González-Sponga, 2005 and Chichiriviche González-Sponga, 2011 are thus newly synonymized with Stenosfemuraia. The genus appears restricted to the Cordillera de la Costa region where the spiders occupy near-ground microhabitats in medium to high elevation forests.